Awareness of Climate Change and Adaptation Strategies Among Secondary School Students in Ogbaru Local Government Area of Anambra State, Nigeria - Oguejiofor, Chidumebi Ngozi; Okafor, Patrick Chinenye; Ani, Anthonia Nwabugo; Nwogbo, Mercy Obianuju; Chukwu, Pius Okechukwu (European Scientific Journal, ESJ, 2025)
This study investigated the awareness of climate change and adaptation strategies among secondary school students in Ogbaru Local Government Area of Anambra State, Nigeria. Two research questions guided, and two null hypotheses were tested at the 0.05 level of significance. The researchers employed a descriptive survey research design. The population consisted of 8,564 JSS and SS students from the 9 public secondary schools in the area. The sample size consisted of 170 students from the four schools sampled for the study using a simple random sampling technique (balloting). Data was collected using the 40-item climate change awareness and adaptation strategies questionnaire (CCASSQ) developed by the researchers and validated by experts. An estimate of the stability of the instrument yielded a reliability coefficient of 0.88 using Cronbach’s Alpha statistic. Mean and standard deviation were used as descriptive statistics, while the independent samples t-test was adopted as an inferential statistic. The findings revealed a high level of awareness of climate change by the JSS and SS students. It also indicated a high level of awareness of climate change adaptation strategies by JSS and SS students in Ogbaru LGA of Anambra State. Based on the findings, it was recommended that the government should strengthen educational infrastructure, such as wind vanes and rain gauges, that could enable the teachers to meet the demands of this era of climate change.